Perlindungan Hukum Pemegang Saham Minoritas dalam Perjanjian Pemegang Saham di Indonesia - Leoni Trika A, Isabella (UNES Law Review, 2023)
In a company, the interests of majority shareholders often take precedence over those of minority shareholders, and shareholder agreements can be used by majorities to regulate matters that primarily benefit them. To safeguard the rights of minority shareholders, they can create several provisions in shareholder agreement. The research question that forms the basis of this paper is: (i) What is the legal status of shareholder agreements in Indonesia?; (ii) What are the general provisions included in shareholder agreements?; and (iii) What special provisions in shareholder agreements offer legal protection for minority shareholders? Ultimately, the following conclusions were reached: (i) Shareholder agreements are legally binding contracts based on Article 1320 of the Indonesian Civil Code; (ii) While there are several general provisions found in shareholder agreements in Indonesia, there are no standard rules governing them; and (iii) The rights of minority shareholders that can be regulated through these agreements include shareholders remedies, rights based on their share class, tag along rights, drag along rights, rights of first offer, and rights of first refusal.